Steps of conservatıon process ın weavıng - Tumbek, Özlem; Zaimoğlu, Ömer (Рroblems of engineering and professional education, 2024)
Carpets and plain woven fabrics, which are one of our tangible cultural heritages, are handcrafted intensively and each of them is a work of design and art in order to transfer our culture and traditions to future generations. It is necessary and very important to protect and preserve these works and to restore damaged ones so that they can be transferred to future generations. Although the production techniques and materials used in the production of carpets and plain weaves are different, their preservation and restoration are similar. In this study, the tools, equipment and process steps used in the storage and restoration of carpets and plain woven fabrics have been tried to be explained by description method, and suggestions have been tried to be made for correct storage and repair.